Traditions of Russian Avant-garde in Teaching Practice at the Turn of the 20th – 21st Centuries (as exemplified in Pedagogical Work of A.V. Kondratyev) - Shlykova, Tatiana V. (Actual Problems of Theory and History of Art, 2013)
At the present moment significant material devoted to artists of the Russian avant-garde traditions is available, nevertheless the distinguishing features of pedagogical system based on the heritage of P.N. Filonov, K.S. Malevich, K.S. Petrov-Vodkin have not still been made subject to thorough research. On the example of A.V. Kondratyev’s pedagogical work discriminating features of drawing and painting teaching practice based on these artistic principles are analyzed. Distinguishing traits of the school are pronounced compositional “frame” in easel painting and extreme stress on the inner structure of the depicted in the study drawing. Stages of study are analyzed consecutively, from the beginner’s level to the level of mature easel painting.
Keywords: analytic art; Russian avant-garde; Leningrad art; pedagogical method